RESPON MASYARAKAT TERHADAP STOP BUANG AIR BESAR SEMBARANGAN (Studi Pada Program Sanitasi Total Berbasis Masyarakat Di Desa Sungai Intan Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir) - Selvy Julia Saputri; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sungai Intan Village Tembilahan Hulu District is one of the villages with the highest rate of open free in the Tembilahan Hulu District area. The community-based total sanitation program has entered the village but there has been no change, the community is still defecating anywhere. This study aims to determine the community towards open defecation free and the factors that influence community response. The method used in this study was quantitative method with cross sectional study design. The population of this research was 725 households. The technique of determining the sample was used the Random Sampling technique with the sample total was 88 households. Data analysis used product moment correlation. The results of the community response study were divided into three categories namely attention, attitude, action. The attention response received a response of 55 people with a percentage of 62.5%. The response of community attitudes got a negative response of 56 people with a percentage of 63.6%. The response of the action got a negative response of 60 with a percentage of 68.2%. Factors related to community response to open defecation in Sungai Intan Village Tembilahan Hulu District Indragiri Hilir Regency sequentially are knowledge with attention response has an r value of 0.516, knowledge with attitude response has an r value of 0.369, knowledge with action response has r value of 0.318, economics with attention response has r value of 0.490, economics with attitude response has value r of 0.379, economy with action response has r value of 0.273, culture with attention response has r value of 0.461, culture with attitude response has r value of 0.328, culture with action responses has an r value of 0.314. Keywords : Response and open defecation free